2007
DOI: 10.1590/s0073-47212007000300016
|View full text |Cite
|
Sign up to set email alerts
|

Population and reproductive features of the western Atlantic hermit crab Pagurus criniticornis (Anomura, Paguridae) from Anchieta Island, southeastern Brazil

Abstract: ABSTRACT. The population of the hermit crab Pagurus criniticornis (Dana, 1852) was studied based on seasonal abundance, size frequency distribution, sex ratio, reproductive period, fecundity and shell relationship. Specimens were collected monthly by SCUBA diving in the infralittoral area of Anchieta Island, Ubatuba. A total of 1,017 individuals was analyzed. Animal size (minimum and maximum shield length, respectively) was 0.7 and 2.9 mm for males, 0.6 and 2.8 mm for non-ovigerous females, and 1.0 and 2.5 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
(44 reference statements)
5
7
0
1
Order By: Relevance
“…These patterns of large males may occur due to different energy requirements for growth between sexes, with males reaching larger sizes than females (Abrams, ). This difference in mean size was also reported for specimens of P. criniticornis in Anchieta Island, São Paulo, Southeastern Brazil, which showed a similar upper size class limit (3.0 mm CSL; Mantelatto, Faria, Iossi, & Biagi, ) to that reported here. For both species, every CSL size class showed similar relative frequencies between males and females.…”
Section: Discussionsupporting
confidence: 88%
“…These patterns of large males may occur due to different energy requirements for growth between sexes, with males reaching larger sizes than females (Abrams, ). This difference in mean size was also reported for specimens of P. criniticornis in Anchieta Island, São Paulo, Southeastern Brazil, which showed a similar upper size class limit (3.0 mm CSL; Mantelatto, Faria, Iossi, & Biagi, ) to that reported here. For both species, every CSL size class showed similar relative frequencies between males and females.…”
Section: Discussionsupporting
confidence: 88%
“…As in other anomurans Mantelatto et al, 2007), males of C. clypeatus inhabiting Pérez Island exhibited a larger body size than females (table I). Usually, body size is viewed as an indicator of ecological dominance.…”
Section: Discussionsupporting
confidence: 71%
“…The lack of ovigerous females in our collection supports this idea. In coastal areas of Brazil, several studies have also shown that male hermit crabs are numerically dominant (Bertini & Fransozo, 1999;Mantelatto et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such variability as observed in Synalpheus apioceros could be due to multiple spawnings during a single reproductive season (Miranda et al 2006, Mantelatto et al 2007). Also, the presence of primiparous females, which tend to produce fewer embryos than multiparous ones (Somerton and Meyers 1983, Mantelatto et al 2007) could explain the variability of embryo number within the same size class.…”
Section: Discussionmentioning
confidence: 96%